Mental health status of children with disorders of sexual development and their correlates - Cai, Jingjing; Zhu, Guochun; Tian, Hongjuan; Yuan, Jinna; Gao, Huihui; Sun, Liying; Dong, Guanping; Ru, Wei; Wu, Dehua; Tang, Daxing; Gao, Weijia; Fu, Junfen; et al. (Frontiers in Public Health, 2022)
Disorders of sexual development (DSD) refer to the congenital abnormalities of chromosomes, gonads, or gender anatomy. Children with DSD usually experience more stress. The present study aims to evaluate the mental health status of children with DSD, and to explore the potential relevant factors. We included 30 children with DSD and 30 age- and gender-matched children without DSD as the control group. All the children and their parents completed the scales of the Hamilton Anxiety Scale (HAMA). Children over 8 years old (n = 22) completed the Screen Scale for Child Anxiety Related Emotional Disorders (SCARED), the Depression Self-rating Scale for Children (DSRSC), and the Egna Minnen av Barndoms Uppfostran-own memories of parental rearing practices in childhood. DSD children had significantly higher somatic anxiety, mental anxiety, and total anxiety scores than the control group (p < 0.001). The scores of the SCARED, anxiety, and depression subscales of DSD children were higher than those of control children (p < 0.05 and p < 0.001, respectively). The correlation analysis showed that the score of generalized anxiety was positively related to age and entertainment. The regression analysis showed that age was a major factor that affected generalized anxiety in DSD children, and neuroticism was a major factor of anxiety disorder and separation anxiety in DSD children. Children with DSD have obvious anxiety problems, which are associated with family environmental factors (entertainment, success, and conflicts) and age. It is important to focus emphasis on emotional stability in children with DSD for detecting anxiety-related emotional disorders early.